Differential Postnatal Expression of Neuronal Maturation Markers in the Dentate Gyrus of Mice and Rats - Radic, Tijana (Front Neuroanat, 2017)
The dentate gyrus (DG) is a unique structure of the hippocampus that is distinguished by ongoing neurogenesis throughout the lifetime of an organism. The development of the DG, which begins during late gestation and continues during the postnatal period, comprises the structural formation of the DG as well as the establishment of the adult neurogenic niche in the subgranular zone (SGZ). We investigated the time course of postnatal maturation of the DG in male C57BL/6J mice and male Sprague-Dawley rats based on the distribution patterns of the immature neuronal marker doublecortin (DCX) and a marker for mature neurons, calbindin (CB). Our findings demonstrate that the postnatal DG is marked by a substantial maturation with a high number of DCX-positive granule cells (GCs) during the first two postnatal weeks followed by a progression toward more mature patterns and increasing numbers of CB-positive GCs within the subsequent 2 weeks. The most substantial shift in maturation of the GC population took place between P7 and P14 in both mice and rats, when young, immature DCX-positive GCs became confined to the innermost part of the GC layer (GCL), indicative of the formation of the SGZ. These results suggest that the first month of postnatal development represents an important transition phase during which DG neurogenesis and the maturation course of the GC population becomes analogous to the process of adult neurogenesis. Therefore, the postnatal DG could serve as an attractive model for studying a growing and functionally maturing neural network. Direct comparisons between mice and rats revealed that the transition from immature DCX-positive to mature CB-positive GCs occurs more rapidly in the rat by approximately 4–6 days. The remarkable species difference in the speed of maturation on the GC population level may have important implications for developmental and neurogenesis research in different rodent species and strains.